ANALISIS PEMAKAIAN BAHAN SUSUN BETON TERHADAP KUAT TEKAN BETON - Eri Setia Romadhon (FTSP Universitas Jayabaya, 2021)
Concrete is the mixed materials between portland cement ,water , coarse aggregate with and without additif. Equivalent in concrete mixture is very important to the means of concrete strength, but there is not accurate to use the concrete mixture with other condition of the strength concrete This research is trying to understand or to know relationship between concrete mixture from Jayabaya university Cimanggis with means of concrete strength. Result from this research, There is a linier relationship between water, sand, semen and split with the correlation above 70 % of means concrete strength.